Study on ionic conduction of carboxymethyl cellulose-kappa carrageenan blend for solid biopolymer electrolytes - Nur Khalidah, Zainuddin (2019)
This thesis presents a detailed investigation of structural and ionic conduction properties of environmentally friendly natural biopolymers electrolyte to overcome polymeric waste disposal faced nowadays. In this research, biopolymer electrolytes (BEs) system comprising carboxymethyl cellulose-kappa carrageenan (CMC-KC) blend biopolymer electrolyte as the host and ammonium nitrate (NH4NO3) as the proton provider was successfully prepared by solution casting technique. The characterizations of the Bes was carried out using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Electrical Impedance Spectroscopy (EIS), and transference number measurement (TNM). The FTIR analysis showed that interaction took place in the CMC-KC polymer blend due to the shifting and appearance of peaks in wavenumbers in the range of 900–2700 cm-1. In addition, there were changes in the peaks with the addition of NH4NO3 in the CMC-KC blend at wavenumbers 828 cm-1, 1047 cm-1, 1322 cm -1, and 3225 cm-1 which corresponded to the symmetric bending (NO3-), vibrational band (NO3-), vibrational band (NH4+), and N-H band of pure NH4NO3 respectively. XRD analysis of the CMC-KC blend revealed that the BEs system has increased in amorphous phase in sample B3 with a ratio of 80:20 of KC, and after NH4NO3 was added in the CMC-KC blend of BEs, the sample S7 that contained 30 wt.% of NH4NO3 showed increased amorphousity supported by the low degree of crystallinity (Xc) and also correlated to the ionic conductivity result. The ionic conductivity was obtained at an optimum value of 3.19 × 10-7 Scm-1 at room temperature when the polymer host was blended with 80:20 ratio of KC. Conductivity was further enhanced to 2.00 × 10-4 Scm-1 with the addition of 30 wt.% of NH4NO3. The conductivity-temperature analysis of all electrolytes was thermally assisted and was found to follow the Arrhenius rule. Dielectric and Modulus studies confirmed that the BEs obeyed non-debye behaviour. Transport study proved that the ionic conductivity was controlled by the diffusion coefficient, D, and ionic mobility,  calculated using ATR-IR deconvolution by employing the Gaussian-Lorentz function adjusted to the Origin Lab 8.0 software. The ionic transference number measurement confirmed that the ion species cation with the highest conduction (S7) was at 0.86. Overall, it is believed that this present BEs system has potential as a new electrolyte candidate in the fabrication of electrochemical devices.